A new genus and new species of Cyclocoelidae (Digenea), a parasite in spotted rail, Pardirallus maculatus (Gruiformes: Rallidae), in the Pampa biome, southern Brazil - Santos, José Junior Dos; Mascarenhas, Carolina Silveira; Müller, Gertrud (Zootaxa, 2023)
Seventeen specimens of the spotted rail, Pardirallus maculatus (Boddaert) (Gruiformes: Rallidae), from the southern Brazil were examined for helminths. Three birds were positive for specimens of Cyclocoelidae (Digenea), which were found in both nasal and abdominal cavities. Helminths were described as Nasuscoelum pampensis n. gen., n. sp. The new genus has an intertesticular ovary forming a triangle with the testis, characterizing the Cyclocoelinae. Nasuscoelum pampensis n. gen., n. sp. is similar to Cyclocoelum mutabile (Zeder, 1800), however it differs from the latter by the presence of vitelline follicles confluence in the posterior region. A revised key to the Cyclocoelinae was proposed to include the new genus.